In vivo schistosomicidal activity of (±)-licarin A-loaded poly(ε-caprolactone) nanoparticles - Lima, Thais C.; Magalhães, Lizandra G.; de L. Paula, Lucas A.; Cunha, Wilson R.; Januário, Ana H.; Pauletti, Patricia M.; Bastos, Jairo K.; Mnuquian, Hallana Alves; Forim, Moacir R.; Morais-Urano, Raquel P.; Laurentiz, Rosangela S. [UNESP]; Tondato, Wellington N. [UNESP]; et al. (Elsevier, 2022)
Schistosomiasis mansoni is an infectious parasitic disease caused by worms of the genus Schistosoma, and praziquantel (PZQ) is the medication available for the treatment of schistosomiasis. However, the existence of resistant strains reinforces the need to develop new schistosomicidal drugs safely and effectively. Thus, the (±)-licarin A neolignan incorporated into poly-Ɛ-caprolactone (PCL) nanoparticles and not incorporated were evaluated for their in vivo schistosomicidal activity. The (±)-licarin A -loaded poly(ε-caprolactone) nanoparticles and the pure (±)-licarin A showed a reduction in the number of worm eggs present in spleens of mice infected with Schistosoma mansoni. In addition, the (±)-licarin A incorporated in the concentration of 20 mg/kg and 200 mg/kg reduced the number of worms, presenting percentages of 56.3% and 41.7%, respectively.
Keywords: Nanotechnology; Schistosoma mansoni, (±)-licarin A